Opportunity to participate in planning and evaluation of support for children with disabilities: Parents' and professionals' perspectives. (March 2020) - Nowak, Herawati I; Broberg, Malin; Starke, Mikaela
A random sample of parents of children with disabilities ( n = 144) from three Swedish municipalities participated in a structured telephone interview including seven questions on child participation and 156 professionals from the same municipalities completed a web-based survey including six questions on child participation. The aim of the study was to explore parents' and professionals' (1) ratings of the opportunities available to children with disabilities to participate in planning, decision-making and evaluation of support and (2) satisfaction with the children's current level of such participation. The results indicated that opportunities for children with disability to participate directly in decision-making processes were limited. Parents and professionals rated older children's opportunities to participate as better compared to younger. Most professionals relied more on parents' descriptions of the child's needs and opinions of support services than on direct communication with the child.